Strategy key thinkers : a critical engagement - Kane, Thomas M. 1969- (Polity Press, 2013)
Strategy: key thinkers expertly introduces the ideas of major strategic thinkers whose work explores the complex challenges associated with the use of military force. Early chapters deal with the foundational work of Sun Tzu (Sunzi), Thucydides, Vegetius, Machiavelli and Carl von Clausewitz and its relevance to problems facing western militaries today. The book then considers broader issues, such as the distinctive importance of air and maritime operations, the difficulty of waging offensive land warfare in the face of modern firepower, the implications of nuclear weapons, and the potential of irregular warfare. It concludes by highlighting key themes which connect - and distinguish - the works under consideration, noting how these similarities and differences can inform the strategic debates of the early twenty-first century"--Back cover